Students' Comprehension of Types of English Presuppositions in Higher Education - Karnedi Karnedi; Silvia Utami (Yayasan Literasi Sains Indonesia, 2022)
A pragmatic viewpoint holds that a sentence's presuppositions govern the types of settings in which it may be felicitously stated (Karttunen, 1974). The purposes of the research were to identify the students’ utterance errors in the understanding of the uses of the types of presupposition and to assess the quantitative numbers of the students’ utterance errors in using presupposition. The data in this research were collected by giving presupposition tests to the students. This research was analyzed quantitatively and qualitatively. There were 25 students were taken as a sample of research. The findings showed that the studen’s ability in uttering presupposition was 51%. (inadequate). The student's ability in classifying the types of presupposition was 67% (Fair). In conclusion, the students found it difficult to comprehend the speaker's meaning of presupposition.